2005
DOI: 10.1002/adma.200501138
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor Photoluminescence from Porous Silicon Using Focused, High‐Energy Helium Ions

Abstract: An image of a dragon is replicated in porous silicon by using 2 MeV helium irradiation prior to electrochemical etching. By careful control of the ion dose at each region, the photoluminescence (PL) wavelength can be tuned to produce a PL image matching that of the original. Results have been explained in terms of ion‐induced changes in the wafer resistivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…The fundamental mechanism for fabrication of porous Si centers around chemical etching [3,4], and while some studies have shown that ion irradiation prior to chemical etching can be used to control certain properties of porous Si [5,6], all porous Si fabrication processes use some combination of anodization or stain etching to produce the porosity in Si. In contrast, dense porous networks have been fabricated in many semiconductor materials, including Ge [7][8][9], GaSb [10][11][12], and InSb [13][14][15], purely by high-energy ion irradiation of the target material.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental mechanism for fabrication of porous Si centers around chemical etching [3,4], and while some studies have shown that ion irradiation prior to chemical etching can be used to control certain properties of porous Si [5,6], all porous Si fabrication processes use some combination of anodization or stain etching to produce the porosity in Si. In contrast, dense porous networks have been fabricated in many semiconductor materials, including Ge [7][8][9], GaSb [10][11][12], and InSb [13][14][15], purely by high-energy ion irradiation of the target material.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been shown that high energy proton beam irradiation prior to electrochemical etching can be used to fabricate precise, three-dimensional microstructures in silicon [13][14][15] and GaAs [16]. In this work, we demonstrate that energetic hydrogen or helium ions can be used to produce controlled light emission from patterned porous silicon [17][18][19]. The advantage of using high energy ions over lower energy, heavier ions used in previous studies is that the range is much deeper and damage is 2-3 orders of magnitude lower.…”
Section: Introductionmentioning
confidence: 91%
“…The technique of focused ion beam has led to several reports showing the patterning of PSi PL (Section 14.4.3.1.1) [44] and photonic structures (Section 14.4.2.2.2) [45][46][47].…”
Section: Effect Of Anodization Conditionsmentioning
confidence: 99%
“…Lateral changes in PL intensity and peak wavelength can be achieved by changing laterally the PS structure or porosity. For example, one could first set up a resistivity pattern (e. g., using focused ion beam [44]) and then perform the anodization, or first make PSi and then induce a two-dimensional pattern by local dissolution of PSi blocks (e.g., using photodissolution with light interference or masking techniques).…”
Section: Photoluminescencementioning
confidence: 99%